2010
DOI: 10.1161/strokeaha.110.580571
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Analysis of Long-Term Exposure to Ambient Air Pollution and the Incidence of Stroke in Edmonton, Alberta, Canada

Abstract: Background and Purpose-Long-term air pollution effects on stroke incidence have not been examined extensively. We investigated the associations between ambient pollution and the incidence of stroke, as well as stroke subtypes, in a northern Canadian city surrounded by energy-sector pollution sources. Methods-Stroke data from an administrative database from 2003 through 2007 were used to estimate annual incidence rates within small geographic regions within Edmonton, Canada. Air pollution levels for each region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 21 publications
2
28
3
1
Order By: Relevance
“…Our incident cases were obtained from a register, which aimed to capture all cases occurring within a defined geographical area, which would have included cases in which death occurred before patients could be admitted and cases that did not attend the hospital, whereas their source was all patients attending emergency departments. With regard to deprivation, the effects of pollutants remained relatively unchanged after adjustment in our study in contrast to the results observed by Johnson et al 28 Possible explanations include the relatively limited range in deprivation across our study area and the lack of correlation between pollutants and deprivation. In addition, we have previously observed a diminishing effect of deprivation on stroke risk with increasing age.…”
Section: Maheswaran Et Al Air Pollution Ischemic and Hemorrhagic Strokecontrasting
confidence: 99%
See 1 more Smart Citation
“…Our incident cases were obtained from a register, which aimed to capture all cases occurring within a defined geographical area, which would have included cases in which death occurred before patients could be admitted and cases that did not attend the hospital, whereas their source was all patients attending emergency departments. With regard to deprivation, the effects of pollutants remained relatively unchanged after adjustment in our study in contrast to the results observed by Johnson et al 28 Possible explanations include the relatively limited range in deprivation across our study area and the lack of correlation between pollutants and deprivation. In addition, we have previously observed a diminishing effect of deprivation on stroke risk with increasing age.…”
Section: Maheswaran Et Al Air Pollution Ischemic and Hemorrhagic Strokecontrasting
confidence: 99%
“…27 In an ecological study carried out in Edmonton, Canada, Johnson et al found no significant associations between a range of air pollutants and ischemic or hemorrhagic stroke after adjustment for area-level deprivation. 28 The geographical areas available for their analysis were relatively large with 1600 to 54 000 households in their areal units in contrast to our study with an average population of 283 people per output area. They had a limited number of pollution monitoring stations available (6 stations for PM 2.5 and 9 for NO 2 ) for interpolating exposure estimates to a large geographical area (approximately 900 km 2 ) containing a population of Ͼ1 All rate ratios adjusted for age (5-year bands) and sex.…”
Section: Discussionmentioning
confidence: 62%
“…The same study showed that there was a 13% increase in this risk when particulate matter concentrations were above 30µg/m 3 6 . Another study in Canada, demonstrated that exposure to air pollution was associated with hospital admissions, particularly in regards to hemorrhagic strokes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…16 However, it is still not clear whether exposure to everyday levels of air pollution over years, decades, or lifetimes promotes the development of stroke in the manner that long-varying exposure to tobacco smoke does. Current evidence is sparse and conflicting, [17][18][19][20][21][22][23] in part due to the lack of cohort data with individual-level assessment of air pollution exposure. A cohort of American women showed an association between long-term exposure to air pollution and stroke incidence, 17 whereas American 18 and Norwegian 19 cohorts failed to detect an association with stroke mortality.…”
mentioning
confidence: 99%
“…20 An English ecological study showed excess risk of stroke mortality and stroke hospital admissions in areas with high levels of air pollution, 21 but a similar Canadian study failed to link emergency department admissions for stroke to air pollu-tion. 22 None of the mentioned studies [17][18][19][20][21][22] distinguished between ischemic and hemorrhagic stroke. A single study found no significant associations with chronic exposure to air pollution in a case-control study of ischemic stroke hospitalizations in Sweden.…”
mentioning
confidence: 99%